Deciphering of the Genetic Control of Phenology, Yield, and Pellicle Color in Persian Walnut (Juglans regia L.) - Marrano, Annarita; Sideli, Gina M.; Leslie, Charles A.; Cheng, Hao; Neale, David B. (Frontiers in Plant Science, 2019)
Yield, nut quality, and ability to adapt to specific climate conditions, are all important factors to consider in the development and selection of new Persian walnut (Juglans regia L.) varieties. The genetic control of these traits is still unknown in walnut, limiting the accuracy and rapidity of releasing new cultivars for commercial use. We studied the genetic architecture of five traits crucial for either marketing (i.e., yield, lateral fruit-bearing, and pellicle color) or selection of individuals with specific phenology (i.e., leafing and harvest date). By combining over 30 years of phenotypic data with genetic profiles generated using the latest AxiomTM J. regia 700K SNP array, we were able to identify and confirm major loci for all these traits. In particular, we revealed that a genomic region at the beginning of Chr1 controls both leafing and harvest date in walnut, consistent with the observed strong phenotypical correlation between these traits, and including candidate genes involved in plant development, leaf formation, and cell division. In addition, a large genomic region on Chr11 that includes genes with a central role in flowering control and shoot meristem growth underlies both lateral fruit-bearing and yield in walnut. We observed a more complex genetic architecture for pellicle color, strongly influenced by the environment (h2 = 0.43). We identified two marker-trait associations on Chr6 and 7 for pellicle color, where genes encoding a UDP-glycosyltransferase or involved in the response to oxidation were found. In conclusion, by combining classical quantitative trait loci (QTL) mapping and genome-wide association mapping, we deciphered, for the first time, the molecular pathways controlling walnut phenology, yield, lateral fruitfulness, and pellicle color. Our findings represent a further milestone in the transition from conventional to genome-assisted breeding in Persian walnut.